1937
DOI: 10.1172/jci100906
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Study of the Action of 10 Commonly Used Drugs on Cardiac Output, Work and Size; On Respiration, on Metabolic Rate and on the Electrocardiogram

Abstract: The possession of a technique which permitted rapid estimations of cardiac output and which, demanding no intelligent cooperation, seemed especially suitable for use on ward patients, has permitted an extensive study on the action of common drugs on the heart and circulation in clinical conditions. This study contains about 450 estimations of cardiac output performed on 85 patients.Coincidentally with these estimations the action of drugs on pulse rate, on blood pressure, on respiratory rate and volume, and on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

1938
1938
1966
1966

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 165 publications
(34 citation statements)
references
References 4 publications
5
29
0
Order By: Relevance
“…Previous work using ballistocardiography and sphygmomanometry, in normal subjects and in patients, has shown only small changes in heart rate, cardiac output, and blood pressure after doses of morphine within the therapeutic range (Starr et at., 1937;Papper and Bradley, 1942;Wangeman and Hawk, 1942;Drew, Dripps, and Comroe, 1946;Denton and Beecher 1949;McCall and Taylor, 1952;Moyer, Morris, and Pontius, 1956;Malt, 1958). The extensive and well-controlled study by Drew et at.…”
Section: Discussionmentioning
confidence: 98%
“…Previous work using ballistocardiography and sphygmomanometry, in normal subjects and in patients, has shown only small changes in heart rate, cardiac output, and blood pressure after doses of morphine within the therapeutic range (Starr et at., 1937;Papper and Bradley, 1942;Wangeman and Hawk, 1942;Drew, Dripps, and Comroe, 1946;Denton and Beecher 1949;McCall and Taylor, 1952;Moyer, Morris, and Pontius, 1956;Malt, 1958). The extensive and well-controlled study by Drew et at.…”
Section: Discussionmentioning
confidence: 98%
“…Cardiac output increased in three of the four cases. This increase is significant in each of these cases, when the difference is judged by the standards which we have set for ourselves (13). In Case W. B. no change of cardiac output during pain was demonstrated, but the blood pressure rose to a level higher than that found in any other case.…”
Section: Resultsmentioning
confidence: 75%
“…An increase in heart rate, cardiac output, and minute ventilation, and a fall in pulmonary vascular resistance occurs in man after the intravenous injection of aminophylline (Fowell, Winslow, Sydenstricker, and Wheeler, 1949;James, Turner, and Merrill, 1948;Starr, Gamble, Margolies, Donal, Joseph, and Eagle, 1937;Storstein, Helle, and Rokseth, 1958;Zimmerman, 1951). In a previous study (Halmagyi and Cotes, 1959) only one subject out of 13 showed an increase in Sao2 after intravenous injection of aminophylline.…”
Section: Discussionmentioning
confidence: 89%